(untitled) (LIS TODAY, 2023)
The progressive advancement of technology, the overflow of information, the unpredictable and unlimited wants of information, the hike of the price of information and the limited capital in the library are the huge challenges modern library is encountering. But despite all those challenges libraries are putting an energy and effort to cope with the challenges. Library provide many services, procure many modern ICT Infrastructure to provide the users the resources they want at the most conveniences and expectation. Understanding the users’ expectations is not that easy as the conception we have. Therefore, this study is conducted to understand the library user’s expectation on ICT infrastructures and library services taking PG Students and Research Scholars of 16 (sixteen) departments of Assam University Silchar, the study area selected by purposive method.